Prescription auditing and drug utilization pattern in a tertiary care teaching hospital of western UP - Abidi, Afroz; Gupta, Surabhi; Kansal, Saurabh; ., Ramgopal (International Journal of Basic & Clinical Pharmacology, 2017)
Background: In India, a proper reporting of medication errors in the hospital is not available. Drugs worth crores of rupee are consumed every year but a substantial part of these drugs are irrationally prescribed. In order to promote rational drug usage standard policies on use of drugs must be set, and this can be done only after the current prescription practices have been audited. The prescriptions were analyzed based on the objectives of the study in order to promote rational use of drugs in a population. Methods: The study was carried out prospectively over a period of two months and 15 days in general medicine OPD of our tertiary care hospital. A specially designed performa was used with pre-inserted carbons. Results: Two hundred and thirty seven prescriptions were analyzed. Total no. of drugs in 237 prescriptions were 1001. Therefore average number of drugs/prescription is 4.22. Drugs were prescribed by generic names in 3.79% of cases, drugs on EDL are only 53.25% and fixed dose combinations are 26.87% of total drugs. Dosage forms used were mostly oral -93.51%. Injectables were only 6.19% and topical forms were least 0.299%. Doctors profile indicates that maximum number i.e. 93.67% were general practitioners. Basic information of patient was written in 72.57% prescriptions. Complete diagnoses were written in 70.04% prescriptions. Only 88.61% prescriptions were legible and only 76.79% prescriptions were complete in terms of dose, route, strength, frequency and dosage forms. Disease pattern seen was variable. Diseases of respiratory system were maximum 44.72 % followed by infectious and parasitic diseases - 16.03 % and diseases of digestive system - 13.92 %. The most common drug groups prescribed were NSAIDs± serratiopeptidases, antibiotics, antihistaminics, multivitamins, minerals, enzymes and expectorants & bronchodilators. The incidence of polypharmacy was also common with maximum number of drugs which were prescribed per prescription were four in 39.24% of prescriptions. The prescriptions also had other minor anomalies. Conclusions: This study showed that there is scope for improvement in prescribing patterns in areas of writing generic names of drugs, essential drugs, writing legible and complete prescriptions. Polypharmacy was also evident from our study. Establishment and implementation of appropriate clinical guidelines, use of essential medicines list, public education about medicines and regular update to the clinicians will help in implementing the principles of rational pharmacotherapeutics.